Parents' views and experiences of talking about autism with their children. (November 2019) - Crane, Laura; Jones, Lydia; Prosser, Rachel; Taghrizi, Morvarid; Pellicano, Elizabeth
The way an autism diagnosis is disclosed to parents has been found to play a crucial role in their acceptance of, and the way they cope with, their child's diagnosis. Yet, research into parents' subsequent experiences of disclosing a diagnosis to their children, and talking to their families about autism more generally, is limited. Using an online survey, the current study examined 558 parents' experiences of talking about autism with their autistic and non-autistic children. Results demonstrated that most parents ( n  = 379, 67.9%) had told their autistic children about their diagnosis. Despite few parents ( n  = 163, 20.4%) receiving advice or support regarding the disclosure of the diagnosis, those that had disclosed felt satisfied with the process ( n  = 319, 84.2%) and felt confident in talking about autism with their children ( n  = 339, 92.4%). Those who had not told their autistic children about the diagnosis largely planned to discuss this with their child in the future ( n  = 100, 73.5%), felt confident in doing so ( n  = 95, 70.9%) and were satisfied with their decision ( n  = 95, 70.4%). Analysis of open-ended data, using thematic analysis, highlighted the importance of openness and the need to tailor explanations to individual children's needs, while acknowledging that disclosure could often be challenging for parents.